Analysis of Committeeless Proof-of-Stake protocol: Searching for a better point of operation - Peixoto, Vinícius; Henriques, Marco Aurélio Amaral (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.235141, 2023)
This work aims to discuss the currently ongoing efforts towards the implementation of a fully autonomous and decentralized consensus mechanism based on Proof-of-Stake. We focus on the technical challenges arising from adopting a committeeless Proof-of-Stake consensus protocol (CPoS) where the global state of the entire peer-to-peer network is used to converge to a distributed consensus instead of relying on a validation committee. Specifically, we analyse the performance and security tradeoffs of the protocol. Since the CPoS protocol is very sensitive to its configuration parameters, we investigate their full impact on the blockchain performance and propose improvements to previous works in the area.